Legal Remedies to Appeal Against Free Verdict in the Crime of Murder - Limehuey, Krisantia Welma; Supusepa, Reimon; Muammar, Muammar (TATOHI: Jurnal Ilmu Hukum, 2026)
Introduction: This article analyzes legal protection for victims of wrongful arrest based on acquittal decisions in criminal murder cases. The case highlights the importance of judicial integrity and accuracy in evaluating evidence to ensure justice and safeguard defendants' human rights in the criminal justice system. Purposes of the Research: This article aims to examine the judges’ legal reasoning in issuing an acquittal and the legal protection available for victims of wrongful arrest. Methods of the Research: This research uses normative juridical methods with a statutory and case study approach, analyzing court decisions and legal literature related to the protection of wrongfully arrested individuals. Findings of the Research: The findings of this study are that the judge handed down an acquittal verdict because there were no two valid evidence found to prove the defendant's guilt in the murder case. The absence of witnesses, weak evidence, and alibi information became the basis for acquittal. Protection for victims of wrongful arrest has not been running optimally and still faces procedural obstacles and a lack of public understanding of their rights. The free verdict emphasizes the importance of fair law enforcement and the need for rehabilitation and compensation for victims of wrongful arrest